2017
DOI: 10.1007/s13205-017-0722-9
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and functional characterization of myxobacteria isolated from soil in India

Abstract: This study reports the isolation of myxobacteria from soil collected from plains in north India. Based on the morphology and 16S rDNA sequence, the isolated myxobacteria were identified as Corallococcus sp., Pyxidicoccus sp., Myxococcus sp., Cystobacter sp. and Archangium sp. The myxobacteria were functionally characterized to assess their ability to produce antibacterial and anticancer metabolites. The isolates were found to be functionally versatile as they produced extracellular bioactive molecules that exh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 46 publications
0
19
0
1
Order By: Relevance
“…The newly isolated strains of myxobacteria (S236, S244, S250, and S252) along with the previously reported strains were identified as protease producers based on the zone of clearance on skim milk agar medium at pH 11.0 ( Kumar et al, 2017 ). All the tested myxobacterial strains produced extracellular proteases.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The newly isolated strains of myxobacteria (S236, S244, S250, and S252) along with the previously reported strains were identified as protease producers based on the zone of clearance on skim milk agar medium at pH 11.0 ( Kumar et al, 2017 ). All the tested myxobacterial strains produced extracellular proteases.…”
Section: Resultsmentioning
confidence: 99%
“…Myxobacteria were isolated as described in Kumar et al (2017) . Briefly, soil samples were placed on E. coli paste spread on water calcium chloride clerigel (WCX clerigel; 0.1% CaCl 2 ⋅2H 2 O, 20 mM HEPES buffer, 0.8% clerigel, and 50 μg/ml cycloheximide; pH 7.2).…”
Section: Methodsmentioning
confidence: 99%
“…The bacteria Pajaroellobacter was identified from soil in earlier study (Kumar et al . ), but its functional role in water remediation has yet to be decoded. Finally, Corynebacterium growth was reported to be linked with higher temperature, whereas slow growth was recorded below 22°C (does not grow at 15°C).…”
Section: Resultsmentioning
confidence: 99%
“…Actinobacteria is an obligate chemoorganotrophs that thrives well on decaying organic matter (Shivlata and Satyanarayana 2015). A study on biodegradation of organic wastes in the ocean found significantly higher percentages of Actinobacteria (55Á9-76Á3%) along with Firmicutes (44Á1-44Á9%) than Proteobacteria (9Á2-15Á5%) (de Leo et al 2012). The positive role of Actinobacteria has been unequivocal for waste water treatment and heavy metal removal from the polluted sites (Wagner and ).…”
Section: Microbial Diversity In Two Different Conditionsmentioning
confidence: 99%
See 1 more Smart Citation